Watching comets - Windsor, Jo (Pearson Education Harlow, 2012)
Watching Comets by Jo Windsor is an engaging children's book that introduces young readers to the fascinating world of comets and their significance in astronomy. The story takes readers on a journey through the night sky, explaining what comets are, how they form, and their historical importance to humanity. Through vivid illustrations and easy-to-understand language, Windsor captures the wonder of observing these celestial objects. The book encourages curiosity about space and science, inspiring children to explore the universe and appreciate the beauty of the cosmos as they learn about the nature of comets and their spectacular appearances.